If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(0) = 8 + 4m Multiply -5 * 0 0 = 8 + 4m Anything times zero is zero. 0 = 8 + 4m Solving 0 = 8 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 0 + -4m = 8 + 4m + -4m Remove the zero: -4m = 8 + 4m + -4m Combine like terms: 4m + -4m = 0 -4m = 8 + 0 -4m = 8 Divide each side by '-4'. m = -2 Simplifying m = -2
| (M+3)(m-4)= | | 56+12x=8+8x | | D=2abc | | 1.5r+15=45r | | -3X+10+4X=13 | | 2ax=10a-3ax | | 8y+8=7y-12 | | 4t-2=33-3y | | 7m+38=5m-16 | | 3y=9-4x | | 3c+17=8 | | 3x-8x-5=-15 | | 5x-17=3x+4 | | 4q+3=-9 | | p-4+-9=p | | 2x(x+3)-7=5(5-x)+7(x+1) | | -5c(4c^2-2c)= | | 8x+(x*x)(x*x)=11 | | ln(16lnx)=2 | | 7+4q=11+3q | | 10x^2+15xy= | | 3(2x-4)=5x+9 | | x+2y+3z=13 | | 3x+29=2 | | 4x+4=-4+2x+12 | | 2abc=d | | 6a+18=30 | | 2x-1=2+2sqrt(x-4)+(x-4) | | 3x+6-8x-9= | | -5(-1)=8+4m | | 3x+2(x-1)=4x+4 | | 9x^2-18x+12=0 |